2019
DOI: 10.1139/cjss-2019-0020
|View full text |Cite
|
Sign up to set email alerts
|

Soil quality and land capability of reclaimed oil and gas well pads in southern Alberta: long-term legacy effects

Abstract: Since 1963 approximately 100 000 oil and gas well pads have been officially certified as reclaimed in Alberta, yet follow-up monitoring programs have not been established to assure provincial environmental desired outcomes such as equivalent land capability are met at these certified well pads. The Ecological Recovery Monitoring Project was designed to determine long-term recovery of environmental quality at certified, reclaimed oil and gas well pads. Our study used soil data from 25 oil and gas well pads that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…Iron chlorosis most often occurs when soil pH is >7 because alkaline soils decrease solubility of cationic nutrients, rendering them less available for absorption and metabolization by tree tissues (Martı́nez & Motto 2000). This was the case on our pads as we, like other investigators, found more alkaline soils compared to forest soils (Osko & Glasgow 2010; Janz et al 2019). We therefore suspect that alkalinity and Fe deficiency could have interacted or contributed independently to arrested succession.…”
Section: Discussionsupporting
confidence: 78%
“…Iron chlorosis most often occurs when soil pH is >7 because alkaline soils decrease solubility of cationic nutrients, rendering them less available for absorption and metabolization by tree tissues (Martı́nez & Motto 2000). This was the case on our pads as we, like other investigators, found more alkaline soils compared to forest soils (Osko & Glasgow 2010; Janz et al 2019). We therefore suspect that alkalinity and Fe deficiency could have interacted or contributed independently to arrested succession.…”
Section: Discussionsupporting
confidence: 78%
“…I used updated versions of some of the algorithms; see Whitson (2017) for details. The ratings were calculated for the soil profile only, similar to the approach followed by Janz et al (2019). Deductions were subtracted from the initial rating of 100 basis points to obtain the final index.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current study findings of no significant difference were contrary to findings by Edwards et al (2014) which noted that mining infrastructure fragments and degrades natural habitat through the creation of roads. Another study conducted by Cui et al (2009) and Janz et al (2019) found out that disturbances can have immediate and persistent or long-lasting effects with slow recovery times on vegetation. The results are also contrary to UNEP (1997), Epstein and Selber (2002), Kumpula et al (2011), OGP/IPIECA (2011) and Kamara et al (2019) whose findings indicated that natural resource extraction of oil and gas exploration had well documented impacts on wildlife as well as vegetation.…”
Section: Vegetation Diversitymentioning
confidence: 99%